2012
DOI: 10.1111/j.1708-8208.2009.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Tomographic, and Histological Assessment of Periosteal Guided Bone Regeneration with Cortical Perforations in Advanced Human Critical Size Defects

Abstract: Periosteal preservation seems to be sufficient as a barrier membrane to protect particulate or block osseous grafts provided that good primary closure is achieved. Bone decortication may enhance clinical and histological outcomes. Graft viability (biopsy specimens) and volume maintenance (CT evaluation) remained stable 35 months post-augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 40 publications
(99 reference statements)
1
43
0
2
Order By: Relevance
“…1A) may affect the healing potential of large defects. The intact periosteum may act as a barrier, allowing guided bone regeneration of the defect 11 . Moreover, this native membrane provides a source of blood supply and nutrients that artificial membranes lack 8,9,11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1A) may affect the healing potential of large defects. The intact periosteum may act as a barrier, allowing guided bone regeneration of the defect 11 . Moreover, this native membrane provides a source of blood supply and nutrients that artificial membranes lack 8,9,11 .…”
Section: Discussionmentioning
confidence: 99%
“…The intact periosteum may act as a barrier, allowing guided bone regeneration of the defect 11 . Moreover, this native membrane provides a source of blood supply and nutrients that artificial membranes lack 8,9,11 . Lemperle et al 19 studied the healing of large calvarial and mandibular defects in mongrel dogs evaluating bone regeneration with and without periosteal preservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A variety of bone grafting or substitutes [2][3][4][5] have been placed in these defects in order to facilitate and/or promote bone healing. However, the problems associated with bone healing followed bone reconstruction may be associated more with systemic skeletal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…By this approach, they gain soft-tissue expansion as well as expansion of the periosteum, with obvious advantages to the subsequent surgical bone augmentation procedures. Verdugo et al (2012) showed that a successful GBR of large bone defects can be achieved by means of cortical perforation and no use of membranes but the periosteum alone. The protocol includes the elevation of a full-thickness mucoperiosteal flap by means of a crestal incision and two vertical releasing incisions, followed by decortication and fixation of autologous bone block grafts.…”
Section: Clinical Applicationsmentioning
confidence: 99%